HAK PENDIDIKAN ANAK DALAM KELUARGA DALAM PANDANGAN IMAM SYAFI’I DAN RELEVANSINYA DENGAN PENDIDIKAN ANAK USIA DINI DI INDONESIA - Wartini, Atik (Musawa Jurnal Studi Gender dan Islam, 2015)
A child’s right to education within the family according to Imam Syafi’i and its significance for early childhood  education in Indonesia This research is based on library research on the rights of the child to education within the family from the viewpoint of Imam Shafi’i, and the impact of his teachings on early childhood education in Indonesia. The study is interesting because the first schools to appear in Indonesia were of the Syafi’i tradition. Imam Syafi’i jurists and ushuliyyin have collections of poems that express the need to develop education in early childhood. Despite this, the theory of children’s education in the school of Imam Syafi’i is under researched. This study examines three research questions. First, how does one undertake a  biography of the thought of Imam Syafi’i and Imam Syafi’i school of thought. Second, what is the concept of children’s rights in the family in the view of Imam Syafi’i. And third, is there reference to  early Childhood education that implies the concept of children’s rights to education in the view of Imam Syafi’i. This study concludes that Imam Syafi ‘i in scientific rihlah is purely academic. Imam Syafi’i also elicits several important ideas on a child’s rights within the family, the right to education and the right to self-expression. Imam Syafi’i schools are relevaant to early childhood education in Indonesia in which these (religious education) schools are widespread.